Direct printing of high-performance micro-supercapacitors on flexible substrates using polymeric stencil masks with highly precise interdigitated patterns - Seong, Kwang Dong; Jung, Jae Yeong; Kang, Jeongmin; Kim, Da Seul; Lyu, Lulu; Seo, Soonmin; Kim, Ju Hyung; Piao, Yuanzhe (Journal of Materials Chemistry A, 2020)
Micro-supercapacitors (MSCs) with a 2D planar architecture are considered as highly promising energy storage devices for state-of-the-art electronics involving highly integrated configurations with versatility. For high-performance operation of MSCs, which can lead to practical applications, high-resolution patterning of electrodes enabling efficient ion-transport is necessary. However, conventional microfabrication normally requires demanding process conditions with low compatibility, and printing technologies as alternatives also need to be further improved for overcoming the low patterning resolution limits. Herein, a direct printing method for realizing high-performance MSCs with highly precise interdigitated patterns is presented. For this work, metal-organic deposition inks and polymeric stencil masks are used for high-resolution printing of electrodes where the inks do not leak into masked areas. Because this method can be adapted to flexible substrates without inducing any structural defect, flexible MSCs are successfully demonstrated with a high resolution of 75 μm. All-printed MSCs in this work exhibit outstanding electrochemical properties in comparison with other existing printed devices, and simultaneously printed multiple MSC arrays are also demonstrated for driving light-emitting diode circuits. It is anticipated that the presented printing platform will spur the development of various multifunctional devices and integrated circuits, which can lead to their further applications.
Keywords: High-performance operation; High-resolution patterning; High-resolution printings; Metal organic deposition; Micro supercapacitors; Multifunctional devices; Planar architecture; Printing technologies